The Relationship of Educational Level to Knowledge Level of High Risk Pregnancy in Integrated Antenatal Care - Reza, Hanif; Puspitasari, Cinthya Dwi Cahyani; Andriani, Nadila Arisa; Suwantari, Saphira Ayu (GLOBAL HEALTH SCIENCE GROUP, 2024)
High risk pregnancy is a risky pregnancy condition that can cause disorders, disease, and even death in the mother and fetus during pregnancy. Integrated antenatal care education is carried out as an effort to provide information and increase knowledge to pregnant women regarding high-risk pregnancies. This study aims to determine the relationship between level of education and level of knowledge regarding high-risk pregnancies in integrated antenatal care carried out during the Month of Service Program at RSIA Ananda Semarang. This study used a pre-experimental design, One-Group Pretest-Posttest Design, then a correlation test was carried out using the Kendall's Tau statistical test to assess the relationship between the research subjects' educational level variables and their level of knowledge. This study is processed using spearment test rank of SPSS. There were 30 participants who met the criteria. The type of data collected is primary data from questionnaire. This questionnaire is a standard questionnaire adopted from Titi Yulianti's research (2020). Research time is from July - August 2022.: In this study, it was found that the majority of subjects were aged between 21-30 years, namely 23 subjects (77%), the majority had normoweight nutritional status, namely 11 subjects (37%). Most parity status was primipara, 16 subjects (53%). The majority of subjects' education level was high school, namely 13 subjects (43%). The average output result obtained from the N-Gain Score analysis is 63.61% which is included in the quite effective category. There is a significant relationship (p=0.000) between the level of education and the level of knowledge regarding high-risk pregnancies. The majority of counseling participants were in the 21-30 year age group, with normoweight, primiparous nutritional status, and high school education level. Integrated antenatal care education is quite effective in increasing pregnant women's knowledge regarding high-risk pregnancies and the level of education has a significant relationship with the level of knowledge the subject has regarding high-risk pregnancies.